Ways to achieve peace in Afghanistan - Chamkani А.; Yesdauletova А.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
One of the first tasks of governments is to provide security for citizens and establish peace in the country. Without peace, no country can achieve social welfare, economic prosperity, and political growth. Therefore, governments are always trying to prevent war and provide lasting peace in their country, but the conflicting interests of some countries cause these countries to go to war. Afghanistan is a country that has been in a constant state of war for the past four decades, and its citizens have been deprived of the blessings of peace and well-being. Although optimism about peace in Afghanistan emerged after the fall of the Taliban regime in late 2001, Pakistan’s continued support for the Taliban has turned it into frustration. The Afghan government’s efforts over the past few years have failed to bring the Taliban to the table and bring peace to Afghanistan for a variety of reasons. This article examines how the Afghan government can use this to achieve peace in the country.